Biophilic Design as a Bridge Between Applied Vastu and Contemporary Interior Design Practice in Urban Indian Residences - Jasmine Ahluwalia; Kuldeep Kumar; Luvditya Khurana; Varish Panchal (International Journal of Architectural Design and Planning, 2026)
The growing disconnect between urban Indian residents and the natural environment has prompted renewed interest in design strategies that restore human–nature connections within indoor spaces. This paper investigates the conceptual and practical convergence between biophilic design—a framework grounded in the innate human affinity for nature—and Vastu, the ancient Indian architectural science that prescribes spatial harmony through alignment with natural forces. Drawing on a qualitative review of existing literature, established biophilic design frameworks, and core Vastu treatises, the study maps specific correspondences between the two systems across six thematic dimensions: orientation and light, natural materials, spatial organization, water integration, ventilation, and green elements. The analysis reveals that numerous principles advocated by contemporary biophilic design—such as daylighting optimization, the use of organic materials, courtyard-based spatial planning, and sensory engagement with natural elements—were already codified within Vastu Shastra centuries ago, albeit in a cosmological rather than empirical register. The paper argues that recognizing these parallels offers Indian interior designers a culturally grounded rationale for implementing biophilic strategies in urban residential projects, particularly in compact apartments where space constraints demand thoughtful adaptation. A conceptual framework is proposed for integrating biophilic and Vastu-informed design strategies in the context of contemporary Indian housing. The findings contribute to the growing body of cross-disciplinary scholarship at the intersection of interior design, architecture, and design pedagogy, and hold implications for curriculum development in Indian design education
Keywords: Biophilic Design; Vastu Shastra; design pedagogy; human–nature connection; interior design; urban Indian residences